ZNF-Mediated Resistance to Imatinib Mesylate in Gastrointestinal Stromal Tumor - Rink, Lori (Public Library of Science, 2013)
Although imatinib mesylate (IM) has transformed the treatment of gastrointestinal stromal tumors (GIST), many patients experience primary/secondary drug resistance. In a previous study, we identified a gene signature, consisting mainly of Kruppel-associated box (KRAB) domain containing zinc finger (ZNF) transcriptional repressors that predict short-term response to IM. To determine if these genes have functional significance, a siRNA library targeting these genes was constructed and applied to GIST cells in vitro. These screens identified seventeen “IM sensitizing genes” in GIST cells (sensitization index (SI) <0.85 ratio of drug/vehicle) with a false discovery rate (FDR) <15%, including twelve ZNF genes, the majority of which are located within the HSA19p12–13.1 locus. These genes were shown to be highly specific to IM and another tyrosine kinase inhibitor (TKI), sunitinib, in GIST cells. In order to determine mechanistically how these ZNFs might be modulating response to IM, RNAi approaches were used to individually silence genes within the predictive signature in GIST cells and expression profiling was performed. Knockdown of the 14 IM-sensitizing genes (10 ZNFs) universally led to downregulation of six genes, including TGFb3, periostin, and NEDD9. These studies implicate a role of KRAB-ZNFs in modulating response to TKIs in GIST.